ANALISIS KEMAMPUAN LABA USAHA PEMBIBITAN KELAPA SAWIT PADA PT. DIAN ABDI NUSA DI KABUPATEN KUTAI BARAT - ., Saparudin (EKONOMIA, 2013)
SAPARUDIN. Faculty Of Economics University 17 August 1945 Samarinda, Analysis Ability Of Income From Operation Seed Coconut of Sawit [At] PT. Oil Lamp Serve Nusa [In] Sub-Province of Kutai West, Under tuition Mr. Prof. Dr. LCA. Robin of Jonathan, MM., M.Si And Father of Heriyanto, SE., MM Â Intention of this writing is to analyse acquirement of income from operation [at] Coconut seed of Sawit [in] PT. Oil Lamp Serve Nusa [In] Sub-Province of Kutai West year 2010, 2011 and 2012.Â In line with this writing, hence told solution fundamental